45‐3: Invited Paper:Summary for: Recent Progress in Highly Efficient Blue TADF Emitter Materials for OLEDs. Issue 1 (May 2017) - Baumann, Thomas; Volz, Daniel
Abstract : After introducing thermally activated delayed luminescence (TADF) conceptually, we give a status report concerning blue OLEDs based on this technology. Great progress was achieved in the last years, allowing for rapid commercialization of this technology. We compare our results to the state of the art as published by academic researchers.